Toward an Understanding of Extracellular tRNA Biology - Torres, Adrian Gabriel; Martí, Eulàlia (Frontiers in Molecular Biosciences, 2021)
Extracellular RNAs (exRNA) including abundant full length tRNAs and tRNA fragments (tRFs), have recently garnered attention as a promising source of biomarkers and a novel mediator in cell-to-cell communication in eukaryotes. Depending on the physiological state of cells, tRNAs/tRFs are released to the extracellular space either contained in extracellular vesicles (EVs) or free, through a mechanism that is largely unknown. In this Perspective article, we propose that ex-tRNAs and/or ex-tRFs are relevant paracrine signalling molecules whose activity depends on the mechanisms of release by source cells and capture by recipient cells. We speculate on how extracellular tRNAs/tRFs orchestrate the effects in target cells, depending on the type of sequences and the mechanisms of uptake. We further propose that tRNA modifications may be playing important roles in extracellular tRNA biology